Proximal Tibial Sliding Osteotomy as an Alternative Solution for Patients With Proximal Tibial Bone Defect After Neglected Tibial Plateau Fractures Undergoing Total Knee Arthroplasty: A Case Report - Riyadli, Muhammad; Mulyadi, Dicky (Indonesian Hip and Knee Society (IHKS), 2022)
Trauma case to the joints, especially the knee joint is a difficult and challenging case to manage. In the initial conditions of trauma, this case may be relatively more rational to do reduction and fixation. However, in cases of delayed treatment, it will be a challenge for an orthopedic, where in the late condition, the knee joint will degenerate earlier and becomes early osteoarthritis. The therapy that can be done depends on the severity of the joint damage itself. One of the actions that can be taken in severe conditions of osteoarthritis is Total Knee Arthroplasty (TKA). But if the defect is very large, a special additional tool is usually needed, which will also be more expensive. We report a 51 years old female patient with secondary osteoarthritis and severe depressed in the medial proximal tibia due to neglected tibial plateau fracture. The patient had a total knee arthroplasty performed with an oblique osteotomy on the medial side of the tibial plateau and shifting it proximally to cover the defect area. The operation went smoothly and the implant used was a primary Posterior Stabilized (PS) TKA implant without metal augmentation. After the procedure, the patient's knee is reassessed. There was improvement in knee deformity, with good stability and full range of motion of the knee. The purpose of this paper is to demonstrate a sliding osteotomy technique for medial proximal tibia in Total Knee Arthroplasty, with the hope of being an alternative solution and reducing additional costs for osteoarthritis cases with a severe defect in the medial proximal tibia.